Eigenvalues of the negative (p, q)-Laplacian under a Steklov-like boundary condition. Issue 4 (3rd April 2019) - Barbu, Luminiţa; Moroşanu, Gheorghe
ABSTRACT: In this paper, we consider in a bounded domainΩ ⊂ R N with smooth boundary an eigenvalue problem for the negative( p, q ) -Laplacian with a Steklov-type boundary condition, wherep ∈ ( 1, ∞ ), q ∈ ( 2, ∞ ) andp ≠ q . A full description of the set of eigenvalues of this problem is provided, thus essentially extending a recent result by Abreu and Madeira related to the( p, 2 ) -Laplacian.